PAIN MANAGEMENT IN LUMBAGO: ROLE OF ACUPUNCTURE IN ADDITION TO LOCAL STEROID INFILTRATION AT TRIGGER POINTS - Bukhari, Syed Zahid Hussain; Zahid, Samina (Journal of Postgraduate Medical Institute, 2011)
Objective: To know the effect of Acupuncture in addition to local steroid infiltration at trigger points in patients of lumbago. Material and Methods: All patients who reported to Pain and Plegia Centre with lumbago were included in the study. Majority among them gave the history of treatment by various surgeons, orthopedic surgeons and neurosurgeons. Patients with caries spine, ankylosing spondylitis and those who had under gone spinal surgery were excluded. Acupuncture and ancillary techniques were used as primary modality to relieve chronic diffuse pain. Trigger spots were identified by deep palpation and were injected with steroid for complete cure. Results: Total number of patients studied was 400. Among them 371 (92.75%) cases of low back pain of muscular origin responded well with complete relief of symptoms. In the remaining 29 (7.25%) cases of low back pain with radiological findings of marginal disc prolapse 20 (5%) recovered completely, four (1%) could live with residual symptoms while 5 cases (1.25%) were uncomfortable and were referred for surgery. Conclusion: Nonspecific chronic low back pain is due to spasm of paraveretebral muscles in the lumbosacral region and its primary cause is trigger spots in the muscles. This spasm is effectively relieved by acupuncture form of treatment unmasking trigger spots, which heal to local pinpointed injections of steroids.